The Learning Trajectory on Integer Operations Material Using Sagele Dance - Hastuti, Intan Dwi; Mariyati, Yuni; Sutarto (Mathematics Education Journal, 2025)
Traditional Indonesian dances can serve as meaningful contexts for mathematics instruction, yet this potential remains underutilized in many classrooms, including in West Nusa Tenggara. This study aims to design a learning trajectory for integer operations by integrating Sagele dance, which features rhythmic forward and backward movements suitable for representing positive and negative numbers. Employing a design research methodology, data were collected through video recordings, field notes, questionnaires, and classroom observations. The study followed three key phases: preliminary design, design experiment, and retrospective analysis. The resulting trajectory consists of three learning activities: (1) exploring free movement in Sagele dance to emphasize directional shifts; (2) combining directional changes to illustrate integer operations; and (3) formalizing these concepts through number line models corresponding to the dance movements. Findings show that integrating the Sagele dance helped students transition from informal to formal mathematical thinking, supporting both conceptual understanding and character development, such as respect for cultural heritage. The cultural contextualization also enhanced student engagement and supported the internalization of abstract operations. This research offers a replicable model for incorporating ethnomathematics into classroom practice. While limited in scope and sample size, the study highlights the promise of culturally grounded learning trajectories in mathematics education and calls for broader application in future research.